Raciocínio lógico formal e aprendizagem em cálculo diferencial e integral: o caso da Universidade Federal do Ceará - Barbosa, Gerardo Oliveira (1994)
Considering the low level of performance historically verified in Calculus I, a compulsory subject to seventeen graduation courses at the Federal University of Ceará, this work has the objective of checking and evaluating intervenient factors of the students´performance in this subject. This study aims at answering the questions to be investigated through the study of the dependent variable - students´ performance in the subject, and of the dependent variables - the relation between the content and teaching level, level of the logical formal reasoning development, interaction level among students, the relation content/specificity of the course, the model of teaching content, and the relation register system/credit system. The population object of this study was made up of students registered in Calculus I in the second semester of 1992. The sample was 97 students calculated for a reliability of 95% and absolute error of 0.5 in the 0........10 scale, taken proportionally according to the distribution of the population by course. A questionnaire of fifteen questions and a logical reasoning test of forty-two items were applied, and secondary data from the Vice-Rectory of Graduation was registered on a filing card. The following conclusions were drawn from the analysis of the data: - the students show a good level of development of the reasoning structures necessary to operate the content of the subject. - in the questions related to the register system\credit system, an interference in the students´ performance was observed, which leads to a fragmentation of the teaching work causing dispersion, discontinuity and heterogeneity, all of which certainly rends effective teaching impossible. - Poor schooling in mathematics is the main reason of the difficulties shown among students in learning the content of the subject. Besides that, they question the traditional way of teaching used by teachers which makes the relation teaching/learning impossible.